The Dynamics of Development In Indonesia: The Perspective of Political-Economy - Andi Yakub (Journal of Research and Multidisciplinary, 2019)
The development process from based on political economy perspectives actually possesses plenty of selections in terms of comprehensive development, models and approaches which could be adjusted into the context of the economy and political development and existence of the ruling regime as its foundation creators. Although the per capita income is increasing every year, but Indonesia's economic growth tends to decline and the poverty rate is still high. This article aims to invite readers to scrutinize again the experience of development which has brought successes and failures, support and resistance, even poverty and prosperity of the people in dynamics aptly named as the “Commander of Development”: politics, economy, and morale of commander.